Childhood anxiety disorder: Pharmacological therapeutic algorithm (Research, Society and Development, 2023)
This is an integrative review that aims to identify an effective pharmacological therapy algorithm for childhood anxiety disorder (ADD). The following descriptors were adopted: anxiety, child health, mental health, psychopathology and health promotion in the journals Latin American and Caribbean Literature on Health Sciences (LILACS), the International Literature on Health Sciences (MEDLINE), the National Library of Medicine National Institutes of Health (PUBMED) and Scientific Electronic Library Online (SCIELO), published between 2000 and 2020. 18 articles were obtained, of which 10 were excluded for not contemplating the proposed theme. Thus, the sample consists of 8 articles that described a pharmacological therapeutic algorithm for IAT, describing the drug classes with emphasis on selective serotonin reuptake inhibitors (SSRIs), tricyclics (ADT) and serotonin and noradrenaline reuptake inhibitors (SNRI) and the use of benzodiazepines in the abortive treatment of anxiety attacks and severe cases of anxiety (refractory to other medications). In view of the underdiagnosis and the high worldwide prevalence, it is understood that it is essential to define a therapeutic algorithm, based on scientific evidence, to promote health in childhood, with a view to providing well-being to the child and his/her family.